Islamic Reconstruction in Spanish (Historical Study) - Hamzah, Saidin (IAIN Parepare, 2022)
This research aims to reconstruct the history of Islam in Spain, the main problem in this research is how Islam is in Spain. The sub-issues raised are 1) how was the process of the arrival of Islam in Spain? 2) How is the development and progress of Islamic civilization in Spain? 3) What factors led to the decline and destruction of Islam in Spain? The aims of the research are: 1) to examine and analyze the arrival of Islam in Spain, 2) to examine and analyze the development and progress of Islamic civilization in Spain, and 3) to reconstruct the factors causing the decline and destruction of Islam in Spain. Research using historical research methods includes Heuristics, source criticism, interpretation,and historiography. The results of the analysis in this study show that: 1) The origin of the arrival of Islam in Spain cannot be separated from the success of Tariq ibn Ziyad in defeating King Roderic, so this victory became the main capital for Tariq ibn Ziyad and his troops to conquer important cities in Spain. 2) Spain is the most important place for Europe in absorbing knowledge developed by Muslims, both in political, socia, and economic relations and civilization between countries. Europeans witnessed the fact that Spain was under Islamic rule far away from other countries in Europe, especially in the field of thought and science,and other physical structures. this area of ​​Spain flows various knowledge to advance and improve all its shortcomings and even achieve its glory until this century.